The reincarnation of an Egyptian queen: Dystopian lateness and speculation in Nina Simone’s Afrofuturism - Elliott, Richard (Jazz Research Journal, 2022)
This article proposes Nina Simone as an Afrofuturist artist who explores themes of utopia and dystopia in connection to posthuman discourses. Having established three main ways in which this is a speculative approach, it then explores gaps in existing theories of posthumanism and Afrofuturism. It also considers work that addresses the omission of female musicians in Afrofuturist theory and proposes alternative theories in the form of speculative fiction and Black utopias. The article discusses Simone’s frequent allusions to Egyptian myth, her self-identification as a ‘robot’ and her interest in other planets, planes and spheres. It argues that, beyond the unexplored parallels with ‘classic’ Afrofuturism, there is a sense of dystopianism, apocalypse and reterritorialization throughout Simone’s mature work. To explore these connections, three case studies are used: the 1969 album Nina Simone and Piano!, the song ‘22nd Century’, and Simone’s performance at the 1976 Montreux Jazz Festival.